HUBUNGAN USIA, PARITAS DAN RIWAYAT HIPERTENSI DENGAN KEJADIAN PREECLAMPSIA BERAT DI RBAPTIS BATU MALANG - Qotimah, Qotimah; Utami, Woro Tri Utami (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2019)
Preeclampsia is an increase in blood pressure that occurs during pregnancy, both Primigravida and Multigravida. Generally it has to do with age, parity and previous history. The purpose of the study was to determine the relationship of age, parity and hypertension history with the incidence of preeklamsia in Batu Baptist Hospital.Quantitative research design with cross sectional approach. The population of all pregnant women with this study sample was preeclampsia mothers. Independent variables are age, parity and history of hypertension. The dependent variable is preeclampsia. The research instrument used was a questionnaire. The study was conducted in January-March 2018. Data analysis used a multiple linear regression analysis model.The results of data analysis showed that the three variables statistically had a significant effect on the occurrence of preeclampsia in pregnant women with a value of F-count > F-table which was 6,788 > 3.16. R-square value of 0.531 means that the three independent variables (X) significantly influence the dependent variable (Y) of 53.1% while the other 46.9% is influenced by other factors not examined.There was no association between age and the incidence of preeclampsia, whereas there was a significant relationship between parity, hypertension history and the incidence of preeclampsia. It is recommended by respondents to maintain a diet and reduce stress, as well as family support.